The role of writing motives in the interplay between implicit theories, achievement goals, self-efficacy, and writing performance - De Smedt, Fien; Landrieu, Yana; De Wever, Bram; Van Keer, Hilde (Frontiers in Psychology, 2023)
It is well established that students' motivation for writing is a key predictor of their writing performance. The aim of the current study is to study and map the relations underlying different motivational constructs (i.e., implicit theories, achievement goals, self-efficacy, and writing motives) and to investigate how these contribute to students' writing performance. For that, 390 Flemish students in stage three of the academic track of secondary education (16-18 years old) completed questionnaires measuring their implicit theories of writing, achievement goals, self-efficacy for writing, and writing motives. Furthermore, they completed an argumentative writing test. Path analysis revealed statistically significant direct paths from (1) entity beliefs of writing to performance avoidance goals (β = .23), (2) mastery goals to self-efficacy for writing (βargumentation = .14, βregulation = .25, βconventions = .18), performance-approach goals to self-efficacy for writing (βargumentation = .38, βregulation = .21, βconventions = .25), and performance-avoidance goals to self-efficacy for writing (βargumentation = -.30, βregulation = -.24, βconventions = -.28), (3) self-efficacy for regulation to both autonomous (β = .20) and controlled motivation (β = -.15), (4) mastery goals to autonomous motivation (β = .58), (5) performance approach and avoidance goals to controlled motivation (β = .18; β = .35), and (6) autonomous motivation to writing performance (β = .11). This study moves the field of writing motivation research forward by studying the contribution of implicit theories, achievement goals, and self-efficacy to students' writing performance, via writing motives.